Exercise loading and bone stucture - Nikander, R. (Studies in Sport, Physical Education and Health, 2009)
The objective of this dissertation was to determine the types of exercise loading that are associated with the strength of bones. Four cross-sectional studies were conducted between 2004 and 2008 including 378 athletes and their 62 referents. Sixteen different Sports were classified into five specific categories for the lower extremities and three categories for the upper extremities according to the type of exercise loading. Besides planar DXA-derived hip structural analysis, pQCT, and MRI methods allowing the assessment of true bone cross-sections were used for the bone structure analyses of the tibia, proximal femur, radius, and humerus. At the lower extremity, the high-impact exercise loading group (volleyball, hurdling, moguls skiing, triple Jump, and high jump) and the odd-impact exercise loading group (soccer, racket games, speed skating, slalom skiing, step aerobics) had 13 to 60% stronger tibia and femoral neck than the reference group. Athletes in high-magnitude exercise loading (weightlifting, powerlifting) did not have more rigid tibia and femoral neck than those in the reference group, while athletes in the repetitive, low-impact loading group (endurance running, orienteering, and cross-country skiing) had some 20 to 30% stronger tibia and their femoral neck also seemed to be 10% stronger than those in the reference group. A novel Unding of this study was that, compared to the reference group, the athletes in the high- and odd-impact exercise loading groups had about 20% thicker cortex at the anterior and supero-lateral regions of the femoral neck, the regions that are especially vulnerable in terms of hip fragility. In the dominant forearm, athletes in both the impact (volleyball and racket games) and high-magnitude (functional weightlifting in soccer and hurdling) exercise loading groups had approximately 15 to 30% stronger radius and humerus than those in the reference group. In the non-dominant forearm, no such difference was found between athletes in impact exercise loading group (racket games) and the reference group, suggesting that there were no substantial inborn differences between these groups. In conclusion, the type of exercise loading seems to be an important external determinant of the structure of bone. At the lower extremity, the rigid bone structure is especially clear among those engaged with high-impact or odd-impact exercise loading, and, at the upper extremity, among those with impact loading in general. However, the Undings of these cross-sectional studies should be tested in randomized controlled trials.